2002
DOI: 10.12968/hosp.2002.63.9.1958
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile xanthogranuloma of the nose in an adult

Abstract: Juvenile xanthogranuloma is a rare benign lesion occurring in infancy and childhood. Despite the term juvenile xanthogranuloma, onset during adulthood can occur with a peak incidence in the second and third decades of life (Tahan et al, 1989). It is characterized by single or multiple cutaneous nodules, which show spontaneous involution. It is commonly mistaken for a malignant lesion. The authors report a case of juvenile xanthogranuloma of the nose in an adult, which was excised for diagnostic and cosmetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…1,3,4,5 Gedela et al and Tan et al reported AXG of nasal columella and nasal ala respectively. 2,6 Similar to our case, these patients presented with slow-growing nasal nodule without any history of nasal obstruction or similar lesion elsewhere. Worden et al described AXG involving the pyriform aperture of the nose in a 73-year-old lady who presented with nasal obstruction.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…1,3,4,5 Gedela et al and Tan et al reported AXG of nasal columella and nasal ala respectively. 2,6 Similar to our case, these patients presented with slow-growing nasal nodule without any history of nasal obstruction or similar lesion elsewhere. Worden et al described AXG involving the pyriform aperture of the nose in a 73-year-old lady who presented with nasal obstruction.…”
Section: Discussionsupporting
confidence: 83%
“…The giant cells are of Touton type, although foreign body type of giant cells may also be present. 2 Early lesions may lack these giant cells. 3 Immunohistochemically, the lesional histocytes are positive for CD68 and negative for S100, CD1a and CD207, thereby differentiating it from Langerhans' cell histiocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…4 The extracutaneous sites frequently involved include the eye (most common), lungs, liver, testes and pericardium, oral cavity, larynx and temporal bone. 2 Histologically, juvenile xanthogranulomas comprise of giant cells, histiocytes, and scarce acute inflammatory cells. Histiocytes, which predominate, commonly contains lipid and grow in solid sheets.…”
Section: Discussionmentioning
confidence: 99%
“…4 Strongly positive immunohistochemical analysis of xanthogranuloma is seen for Factor XIIIa, KP1, KiM1P, HAM 56, HHF 35, and vimentin, whereas S-100 protein, anti-Macrophages antibody (MAC 387), Leu M1, and desmin show a negative result. 2,7 Histiocytosis X has a close resemblance to juvenile xanthogranuloma. It is characterized by the presence of indented nuclei with invasion of the overlying epidermis seen on light microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive review of the English-language literature revealed only 1 other case with this presentation in an adult. 1 We discuss this interesting case and present a brief review of the disease process.…”
mentioning
confidence: 99%